Sanation of vivarium air with a help of ultraviolet emission - Свінтицька, К. В. (Scientific Progress & Innovations, 2012)
The possibility of using ultraviolet bactericidal irradiator of closed type «Fiolet-T04» for sanitization in the poultry’s accommodation in bird’s presence hasben shown. Optimal operating conditions of this irradiator and its use for the sanitization of the poultry’s accommodation have been determined. It is The substantial disinfectant effect of this irradiator on the general germ pollution in the poultry-houses (quantity of the microorganisms decreased by 28 %) and absence of the bad influence on the poultry have been also determined.